(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This article examines the foundations of investment financing in Uzbekistan, its theoretical aspects, and promising directions. Investments play a key role in the country’s economic development, contributing to industrial growth and improving the population’s living standards. The article examines current trends, theoretical concepts, and organizational foundations of investment financing, taking into account Uzbekistan’s national context and international experience. The article also discusses existing problems and suggests ways to solve them, including the role of equity financing (share financing) in expanding investment opportunities.